Synthesis and characterizations of chromium-aluminium mixed oxides catalysts to produce fame / Sophia Lenja Roger ... [et al.] - Roger, Sophia Lenja; Wan Kamis, Wan Zuraida; Isa, Norain; Ali Bashah, Nur Alwani; Inderan, Vicinisvarri (Universiti Teknologi MARA, Pulau Pinang, 2022)
Biodiesel or fatty acid methyl ester (FAME) is a clean-burning renewable fuel that is alternative to petroleum fuel. In this study, chromium–aluminium (Cr-Al) mixed oxides were synthesized, characterized and used as catalyst in the transesterification of cooking palm oil (CPO) to produce FAME. The reactions were conducted in a batch reactor at temperature of 160 °C for 3 h. The effects of catalyst synthesis conditions, which are metal ratio and calcination temperature were studied. The metal ratio Cr:Al of 1:1, 2:1, 0:1 and 1:0 and calcination time between 400 °C and 600 °C contributed effects on the FAME density obtained from the reaction. The catalyst characteristics in terms of surface area, pore size, pore volume and thermal stability and surface functional groups were also affected by the various metal ratio and calcination temperature. The results showed that Cr:Al prepared at 1:1 metal ratio and calcined at 500 °C exhibit FAME density of 860 kg/m3, which is within the value range of biodiesel fuel density. The catalyst has surface area of 105.00 m2/g, pore size of 32.81 Å and pore volume of 0.086 cm3/g sufficient to promote efficient heterogenous catalytic activity and has good thermal stability. Thus, Cr-Al mixed oxides has potential as heterogeneous catalyst to produce FAME from the transesterification of CPO